PREJUDICE TOWARDS SKIN COLOR IN FILM FRUITVALE STATION BY RYAN COOGLER - Putra Putra (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This research examines the prejudice based on skin color depicted in the film Fruitvale Station (2013) by Ryan Coogler. Utilizing qualitative methods and integrating the intrinsic elements of fiction approach with Nelson Todd and Michael Olson's prejudice theory. The study focuses on Oscar’s characterization as a young African-American man burdened by societal biases, culminating in his unjust death. By not excluding other elements in the intrinsic structure, it is impossible to do so because each element has a close relationship in forming a unified literary work. The research highlights the impact of racial prejudice on Oscar Grant, the main character, who faces systemic injustice and stereotypes despite his efforts to improve his life. The prejudice theory reveals how cognitive, affective, and behavioral dimensions of prejudice contribute to stereotypes and structural inequality. The findings underscore the destructive consequences of racial prejudice on individuals and society. This research confirms that skin colour prejudice in America, as experienced by Oscar Grant, is still a real danger that significantly impacts people's lives. This theme is not only relevant in the context of Oscar Grant, but also highlights the need for deeper social awareness to eliminate prejudice and discrimination